HUBUNGAN OBESITAS DENGAN KEJADIAN KANKER PAYUDARA DI RSUD BANGKINANG - Ria Irena (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
Breast cancer is a breast disorder that is most feared by women, because this disease cannot be cured when found at an advanced stage. The WHO report in 2005 reached 1,150,000 women and 700,000 thousand lived in developing countries, including Indonesia. Obesity factors cause a 30% risk of cancer. In Riau, based on data from the medical record processing section of RSUD Bangkinang, the incidence of breast cancer was the fourth highest occurrence in the general surgery section. The purpose of this study was to analyze the relationship of obesity to the incidence of breast cancer in RSUD Bangkinang. The type of research used was analytic with a case control approach using secondary medical record data at RSUD Bangkinang. The population were all patients who had breast cancer RSUD Bangkinang Samples were taken using simple random sampling technique so that 79 respondents were obtained as cases and 79 respondents as controls. Data analysis in this study was univariate and bivariate using the chi square test. The results showed that there was a significant relationship between obesity and breast cancer (p = 0.011). The hospital is able to provide communication, information and education (IEC) media about breast cancer so that breast cancer can be detected early